Avaliação de métodos de estimativa de evaporação no reservatório Armando Ribeiro Gonçalves em Itajá/RN - Medeiros, Aline Daniele Lucena de Melo (Universidade Federal Rural do Semi-Árido, 2019)
The knowledge of water losses by evaporation on a water-free surface in the reservoirs n the arid and semi-arid regions is of fundamental importance in the of water resources for different usings, whether in agricultural production, agroindustrial, domestic supply and etc. The purpose of this study is to compare the methods of estimating water osses used by Linacre simplified (1977), ), Linacre (1993), Kohler et al., (1955) and Thorntwaite (1948), and compare with the model of Penman et al., (1948) used as a standard, so to know more precisely which is the best to be used to estimate the evaporation in the reservoirs that have free surface. However, this work may help to determine daily evaporation losses, thus facilitating knowledge for future research purposes. The results showed that: a) the average annual evaporation in the reservoir of the Dam Armando Ribeiro Gonçalves in Itajá-RN, estimated by the model of Penman (1948) was from 1.746,61mm, overestimated by Linacre (1977) and underestimated by Kohler et al., (1955), evaporation of 2.237,23 mm, 1.452,97 mm, respectively; b) The average equivalent flow of the five models analyzed, due to the evaporation to the Armando Ribeiro Gonçalves Dam is 3,81 m³ s-¹ ; The equivalent flow corresponding to the evaporation losses of the free surface of the Armando Ribeiro Gonçalves Dam corresponds to 32.4% of the regularization flow, and; d) The use of mathematical models, in the calculation of free surface evaporation in reservoirs to obtain equivalent flows, is a great tool for monitoring watersheds.
Monografia
Keywords: Recursos hídricos; Evaporação; Barragem; Monitoramento; Water resources; Evaporation; Dam; Monitoring; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA